Effect of Fe content on microstructure and mechanical properties of Al-Mg-Si alloy - LIU Hui; FU Yilei; CHEN Zongqiang; WANG Hailong; CHENG Liqiang; ZHOU Zhiyu; ZHANG Jingliang (Journal of Aeronautical Materials, 2023)
The effect of Fe content on the microstructure and mechanical properties of Al-Mg-Si alloy cast rods at different solution temperatures was investigated by means of electronic tensile testing machine, metallographic microscope and transmission electron microscope. When Fe content is 0.14%（mass fraction, the same below）, Al-Mg-Si alloy has the highest strength and elongation. With the increase of solution temperature, the strength of the alloy increases continuously. When the solution temperature is above 520 ℃, the strength of the alloy tends to peak, the tensile strength is 280 MPa, the yield strength is 259 MPa, and the elongation is 13.40%. For the Al-Mg-Si alloy with Fe content of 0.14%, the Fe-rich phase at the grain boundary is spherical α-Al8Fe2Si, which has a weak cleavage effect on the alloy matrix, and its dispersion distribution plays a role in the grain boundary binding. When Fe content is lower than 0.14%, the spherical α-Al8Fe2Si at grain boundaries is very little, and the nailed grain boundaries are weak. When the solution above 500 ℃, the grains grow obviously, the elongation after fracture is greatly reduced. When the Fe content is higher than 0.14%, the Fe-rich phases are mostly long strips of β-Al5FeSi, which have a strong effect on the interface cleavage. With the increase of Fe content, the strength and post-fracture elongation of the alloy decrease continuously. In addition, Fe content affects the precipitation transition during the aging process of βʺ phase. When Fe content is 0.14%, the size of βʺ phase precipitation is small, the number is large, and the distribution is dense, which has the strongest hindering effect on dislocation movement.